Tumor microenvironment responsive FePt/MoS2 nanocomposites with chemotherapy and photothermal therapy for enhancing cancer immunotherapy. Issue 42 (10th October 2019) - Zhang, Dongsheng; Cui, Ping; Dai, Zhichao; Yang, Baochan; Yao, Xiuxiu; Liu, Qingyun; Hu, Zunfu; Zheng, Xiuwen
Abstract : As a multifunctional platform for photo-chemo-immunotherapy strategies, FePt/MoS2 nanocomposites shows great potential in cancer theranostic. Abstract : The metastasis and recurrence of tumors are the main reasons for cancer death. In this work, a promising therapy for tumor treatment that can eliminate primary tumors and prevent tumor relapses is introduced by combining chemotherapy, photothermal therapy (PTT) and immunotherapy. Multifunctional FePt/MoS2 -FA nanocomposites (FPMF NCs) were obtained via anchoring FePt nanoparticles and folic acid (FA) on MoS2 nanosheets. As an efficient ferroptosis agent, FePt nanoparticles could catalyze the Fenton reaction to produce the reactive oxygen species (ROS). Through the highly effective photothermal conversion of MoS2 nanosheets, the primary tumor cells could be ablated by photothermal therapy (PTT). Moreover, the metastatic tumors were eliminated effectively with the help of oligodeoxynucleotides containing cytosine–guanine (CpG ODNs) combined with systemic checkpoint blockade therapy using an anti-CTLA4 antibody. Even more intriguingly, a strong immunological memory effect was obtained by this synergistic therapy. Taking all these results into consideration, we anticipate that the photo-chemo-immunotherapy strategies show great promise toward the development of a multifunctional platform for anticancer therapeutic applications.